(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Using job satisfaction as a mediating element, this study looked at the efficacy of rewards and recognition as a retention strategy for employees. Regression and mediation analysis were used to find out the association between rewards, recognition, motivation, work satisfaction, and employee retention. This research was conducted with 150 employees at Algonox Technologies in Hyderabad. From the work it was found that while recognition has a considerable detrimental influence on retention, rewards have major beneficial impact. Retention may increase when incentives and acknowledgment are coupled. It was discovered that a strong mediator of the association between incentives, recognition, retention, and rewards was job satisfaction. The report contends that funding initiatives that honor, commend, and inspire employees can lead for higher job satisfaction and, in turn, strengthen staff retention.